Tumor-Derived Extracellular Vesicles: Modulation of Cellular Functional Dynamics in Tumor Microenvironment and Its Clinical Implications - Santos, Nathalia Leal; Bustos, Silvina Odete; Bhatt, Darshak; Chammas, Roger; Andrade, Luciana Nogueira de Sousa (Frontiers in Cell and Developmental Biology, 2021)
Cancer can be described as a dynamic disease formed by malignant and stromal cells. The cellular interaction between these components in the tumor microenvironment (TME) dictates the development of the disease and can be mediated by extracellular vesicles secreted by tumor cells (TEVs). In this review, we summarize emerging findings about how TEVs modify important aspects of the disease like continuous tumor growth, induction of angiogenesis and metastasis establishment. We also discuss how these nanostructures can educate the immune infiltrating cells to generate an immunosuppressive environment that favors tumor progression. Furthermore, we offer our perspective on the path TEVs interfere in cancer treatment response and promote tumor recurrence, highlighting the need to understand the underlying mechanisms controlling TEVs secretion and cargo sorting. In addition, we discuss the clinical potential of TEVs as markers of cell state transitions including the acquisition of a treatment-resistant phenotype, and their potential as therapeutic targets for interventions such as the use of EV inhibitors to block their pro-tumoral activities. Some of the technical challenges for TEVs research and clinical use are also presented.